Equality vs. differentiation: on solidarity and justice in social law - Lach, Eryk (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2016)
The paper describes the question of the principle of equality in social law against the background of permissible differentiation and its justification. The author refers to the axiology of social law as an instrument of social policy by presenting the function of social law. He discusses the question of social justice as distributive justice, and defines the principle of social solidarity and the principle of the common good as the most important for the healthcare system.